Comparative Genomic Analysis Reveals Extensive Genetic Variations of WRKYs in Solanaceae and Functional Variations of CaWRKYs in Pepper - Cheng, Yuan; Ahammed, Golam Jalal; Yao, Zhuping; Ye, Qingjing; Ruan, Meiying; Wang, Rongqing; Li, Zhimiao; Zhou, Guozhi; Wan, Hongjian (Frontiers in Genetics, 2019)
As a conserved protein family, WRKY has been shown to be involved in multiple biological processes in plants. However, the mechanism of functional diversity for WRKYs in pepper has not been well elucidated. Here, a total of 223 WRKY members from solanaceae crops including pepper, tomato and potato, were analyzed using comparative genomics. A tremendous genetic variation among WRKY members of different solanaceous plants or groups was demonstrated by the comparison of some WRKY features, including number/size, group constitution, gene structure, and domain composition. The phylogenetic analysis showed that except for the known WRKY groups (I, IIa/b/c/d/e and III), two extra WRKY subgroups specifically existed in solanaceous plants, which were named group IIf and group IIg in this study, and their genetic variations were also revealed by the characteristics of some group IIf and IIg WRKYs. Except for the extensive genetic variations, certain degrees of conservatism for solanaceae WRKYs were also revealed. Moreover, the variant zinc-finger structure (CX4,7CX22-24HXC) in group III of solanaceae WRKYs was identified. Expression profiles of CaWRKY genes suggested their potential roles in pepper development and stress responses, and demonstrated a functional division pattern for pepper CaWRKYs. Furthermore, functional analysis using virus induced gene silencing (VIGS) revealed critical roles of two CaWRKYs (CaWRKY45 and CaWRKY58) in plant responses to disease and drought, respectively. This study provides a solid foundation for further dissection of the evolutionary and functional diversity of solanaceae WRKYs in crop plants.